A comprehensive behavioral evaluation in the lithium–pilocarpine model in rats: Effects of carisbamate administration during status epilepticus. Issue 7 (11th May 2013) - Faure, Jean‐Baptiste; Akimana, Gladys; Carneiro, José E. M.; Cosquer, Brigitte; Ferrandon, Arielle; Geiger, Karin; Koning, Estelle; Penazzi, Lorène; Cassel, Jean‐Christophe; Nehlig, Astrid
Summary Purpose Administration of carisbamate during status epilepticus (SE) prevents the occurrence of motor seizures in the lithium–pilocarpine model and leads in a subpopulation of rats to spike‐and‐wave discharges characteristic of absence epilepsy. Widespread neuroprotection accompanied this change in seizure expression. To assess whether these carisbamate‐induced changes affected comorbidity, we used a large battery of behavioral tests in rats that had developed temporal lobe or absence‐like seizures. Methods Lithium–pilocarpine or saline was administered to 60 adult rats. Carisbamate (90 mg/kg) or diazepam and saline was given 1 h after SE onset, and repeated 8 h later and twice daily over 6 more days. Rats were video‐monitored for 2 months. Subsequently, locomotor activity, anxiety, and various types of memory were assessed. Key Findings In rats with motor seizures, treated or not with carisbamate, all features of behavior were impaired compared to controls. Rats exhibiting absence‐like seizures after carisbamate treatment behaved as controls in all paradigms tested along with widespread neuroprotection. Significance Carisbamate treatment leading to absence‐like instead of temporal lobe seizures impressively prevented behavioral comorbidities reported by patients with epilepsy as the most disabling.